A Double-Blind, Placebo-Controlled Study of the Omega-3 Fatty Acid Docosahexaenoic Acid in the Treatment of Major Depression - Marangell, Lauren B.; Martinez, James M.; Zboyan, Holly A.; Kertz, Barbara; Kim, H. Florence Seung; Puryear, Lucy J. (The American journal of psychiatry, 2003)
OBJECTIVE: This study was an evaluation of the omega-3 fatty acid docosahexaenoic acid (DHA) for the treatment of major depression. METHOD: Thirty-six depressed patients were randomly assigned to receive DHA, 2 g day, or placebo for 6 weeks. Response was defined a priori as a ≥50% reduction in the score on the Montgomery-Åsberg Depression Rating Scale. Thirty-five participants were evaluable; 18 received DHA, and 17 received placebo. RESULTS: Response rates were 27.8% in the DHA group and 23.5% in the placebo group. The difference in response rates between groups did not reach statistical significance. CONCLUSIONS: This trial failed to show a significant effect of DHA monotherapy in subjects with major depression.